2021
DOI: 10.3899/jrheum.200967
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Disease Activity Indices in Spondyloarthritis From the Sex Perspective: A Systematic Review and Metaanalysis

Abstract: Objective To determine whether the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Disease Activity Score (ASDAS) exhibited differences between women and men. Methods We systematically searched MEDLINE, Embase, Web of Science and other sources in English or Spanish from 01 January 1995 to 31 July 2020, to assess the differences according to sex in BASDAI and ASDAS. We performed a comparative analysis by sex using t-student test and mean difference by sex meta-analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
(295 reference statements)
2
5
0
Order By: Relevance
“…Differences in disease activity between sexes have been reported in patients with axSpA. Previous studies have also reported significant differences in BASDAI between males and females, similar to this study, whereas no significant differences were observed in ASDAS [ 12 , 27 , 28 ]. The specific reasons for variations in disease activity between men and women are not completely understood.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Differences in disease activity between sexes have been reported in patients with axSpA. Previous studies have also reported significant differences in BASDAI between males and females, similar to this study, whereas no significant differences were observed in ASDAS [ 12 , 27 , 28 ]. The specific reasons for variations in disease activity between men and women are not completely understood.…”
Section: Discussionsupporting
confidence: 88%
“…In BASDAI, the weight of the questions for both peripheral arthritis and enthesitis is set at 20%. However, in ASDAS, the weight for peripheral arthritis (tender and swollen joints) was set to approximately 10.4%, and there was no independent question for enthesitis [ 28 ]. Therefore, it is possible that BASDAI is more sensitive in distinguishing differences in peripheral manifestations than ASDAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a recent systematic review and metanalysis showed that BASDAI was higher in females, but no differences in the ASDAS were detected, suggesting that the two most widely used indices of disease activity in axSpA discriminate differently according to gender ( 14 ), as we disclosed in our study. The authors proposed that this is most likely because of their differences in their components and the relative weight of them in the final score, which would result in different BASDAI and ASDAS scores depending on the presence/absence of different disease manifestations ( 14 ). Females in our study had more peripheral manifestations and significatively higher scores for fatigue, spinal pain, joint pain/swelling and localized tenderness than males.…”
Section: Discussionsupporting
confidence: 63%
“…Regarding peripheral manifestations, the question about joint pain/swelling has a lower weight in the ASDAS score than in the BASDAI index and the presence of enthesitis, more frequent and severe in females, is not included in ASDAS, but it is in BASDAI, as the fourth question of BASDAI is considered as a proxy for enthesitis ( 15 ). All these clinical differences could at least partially explain why ASDAS may not be sensitive enough to detect gender differences in disease activity ( 14 , 16 ). We acknowledge that ASDAS is the preferred and most recommended index to evaluate disease activity nowadays, for different reasons ( 17 ).…”
Section: Discussionmentioning
confidence: 99%